Relationship between training workloads, match workloads, and match performance in elite netball - Simpson, M. J.; Jenkins, D. G.; Connick, M.; Kelly, V. G. (International Journal of Sports Physiology and Performance, 2022)
Purpose: This study examined the relationships between training workloads, game workloads, and match performance in an elite netball team.